Epidemiology of endometriosis and its comorbidities. (February 2017) - Parazzini, F.; Esposito, G.; Tozzi, L.; Noli, S.; Bianchi, S.
Abstract: Genetic profile, inflammation, hormonal activity, menstrual cyclicity, organochlorine burden, prostaglandin metabolism and immunological factors have been suggested to play a role in the establishment and development of endometriosis. From the epidemiological perspective, several risk factors have been studied to suggest or support the different aetiological hypotheses. Social class and family history apart, the factors most consistently associated with endometriosis are early age at menarche and long and heavy menstrual cycles. These menstrual characteristics (together with nulliparity) reflect increased exposure to menstruation. The other main risk factors are pigmentary traits and sun habits, alcohol intake, use of oral contraceptives, and environmental factors such as exposure to polychlorinated biphenyls and dioxin. All of these factors support a potential role of hormonal mileau and inflammation in the pathogenesis of endometriosis. There is a clear association between endometriosis and gastrointestinal and immunological diseases, ovarian cancer and other gynaecological cancers, and thyroid cancer.